Optimization of superior esq and hr On the preparation of demographic bonus In the era of the industrial revolution 4.0 - Eka Nur Janah; Iskandar Ritongah; Nurhayati Nurhayati (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2021)
The focus of this study is how to optimize superior ESQ and HR that can provide readiness to face the demographic bonus in Indonesia today and in the era of the industrial revolution 4.0.The writing of this research was carried out using descriptive qualitative writing using an in-depth literature study. The data collection method used is the method of literature, documentaries, subjective intuition. The process of data analysis is carried out by collecting data, presenting data, analyzing, and discussing.The results of this study are optimizing superior and quality HR by increasing the ESQ as a basis which is sufficient to provide a positive side in preparing for the demographic period, as well as providing increased quality in the face of the industrial revolution 4.0 era.